Development and Validation of a Syndrome Definition to Identify Suspected Nonfatal Heroin-Involved Overdoses Treated in Emergency Departments. Issue 4 (July 2021) - Scholl, Lawrence; Liu, Stephen; Vivolo-Kantor, Alana; Board, Amy; Stein, Zachary; Roehler, Douglas R.; McGlone, Londell; Hoots, Brooke E.; Mustaquim, Desiree; Smith, Herschel
Abstract : Context: The Centers for Disease Control and Prevention (CDC) works closely with states and local jurisdictions that are leveraging data from syndromic surveillance systems to identify meaningful changes in overdose trends. CDC developed a suspected nonfatal heroin overdose syndrome definition for use with emergency department (ED) data to help monitor trends at the national, state, and local levels. Objective: This study assesses the percentage of true-positive unintentional and undetermined intent heroin-involved overdose (UUHOD) captured by this definition. Design/Setting: CDC applied the UUHOD definition to ED data available in CDC's National Syndromic Surveillance Program (NSSP). Data were analyzed from 18 states that shared access to their syndromic data in NSSP with the CDC overdose morbidity team. Data were analyzed using queries and manual reviews to identify heroin overdose diagnosis codes and text describing chief complaint reasons for ED visits. Measures: The percentage of true-positive UUHOD was calculated as the number of true-positives divided by the number of total visits captured by the syndrome definition. Results: In total, 99 617 heroin overdose visits were identified by the syndrome definition. Among 95 323 visits identified as acute heroin-involved overdoses, based on reviews of chief complaint text and diagnosis codes, 967 (1.0%) were classified as possible intentional drug overdoses. Among all 99 617 visits, 94 356 (94.7%) were classified as true-positive UUHOD; 2226 (2.2%) and 3035 (3.0%) were classified as "no" and "maybe" UUHOD, respectively. Conclusion: Analysis of the CDC heroin overdose syndrome definition determined that nearly all visits were captured accurately for patients presenting to the ED for a suspected acute UUHOD. This definition will continue to be valuable for ongoing heroin overdose surveillance and epidemiologic analysis of heroin overdose patterns. CDC will evaluate possible definition refinements as new products and terms for heroin overdose emerge. Abstract : Supplemental Digital Content is Available in the Text.